A comprehensive approach to green roof typology forming in the context of eco-friendly construction standardization - Kushniruk, T. M.; Petryshche, О. І.; Dodurych, V. V. (Man and Environment. Issues of Neoecology, 2025)
Purpose. Development of a green roof classification system adapted to the climatic, architectural, and regulatory conditions of green construction in Ukraine, taking into account architectural, spatial, functional, environmental, and social factors.Methods. Systemic-structural, and case analysis were used, as well as comparative-analytical, classification-typological, synthetic, and matrix-rating methods.Results. A multi-level classification of green roofs is formed according to the degree of exploitation, intensity of greening, location, and social accessibility. The developed system allows systematizing the structural, functional, and environmental parameters of green roofs. The scientific novelty lies in the creation of a nationally adapted typology of green roofs as an element of the greening of the built environment. The practical significance lies in the possibility of using the results to develop standards and regulatory documents, and the research prospects include further integration of the classification into green building standards.Conclusions. It has been proven that the expanded systematization of green roof typology contributes to the improvement of green building standards, increased energy efficiency of buildings, preservation of biodiversity, and the formation of an environmentally and socially oriented urban environment.